The endocrine spectrum of Rathke cleft cysts - Rzewuska, Natalia; Kunicki, Jacek; Kunicki, Michał (Frontiers in Endocrinology, 2025)
Rathke cleft cysts (RCCs) are rare non-neoplastic lesions of the pituitary gland. Usually, these cysts are small and remain asymptomatic clinically. For unknown reasons, in some cases, RCCs enlarge and cause symptoms such as headaches, visual disturbances, and pituitary gland dysfunctions. The literature lacks comprehensive reviews or guidelines that summarize clinicians’ knowledge about hormonal assessment in symptomatic cases. We present a review of the literature focused on symptomatic cases of RCCs, manifesting with hormonal imbalance. Hormonal symptoms occur in 19.4–81% of symptomatic cases. The most common hormonal dysfunction is hyperprolactinemia, found in even 46% of cases, and the second most frequent is hypogonadism. The improvement after surgery is hesitant, between 19% and 67.8%, and is the worst in secondary hypothyroidism. In the pediatric patient group, hormonal dysfunctions are the most common presentation of such a lesion. Dysfunction of the posterior pituitary gland in the course of symptomatic RCCs can result in treatment-resistant arginine vasopressin deficiency and syndrome of inappropriate antidiuretic hormone secretion. It should be emphasized that among the endocrine disorders of RCCs in young premenopausal women, menstrual disorders and related fertility problems are prevalent. Irregular menstrual cycles or amenorrhea are reported in up to 17% of symptomatic RCCs. Endocrinologists and neurosurgeons must be acutely aware of hormonal imbalances in RCCs and conduct hormonal evaluations in every case of symptomatic RCC to enhance the management of these lesions. Guidelines for managing symptomatic cases of RCC are necessary to improve patient care and outcomes.